Quantifying physical decline in juvenile neuronal ceroid lipofuscinosis (Batten disease) - Kwon, J.M. (Lippincott Williams & Wilkins, 2011)
OBJECTIVE: To use the Unified Batten Disease Rating Scale (UBDRS) to measure the rate of decline in physical and functional capability domains in patients with juvenile neuronal ceroid lipofuscinosis (JNCL) or Batten disease, a neurodegenerative lysosomal storage disorder. We have evaluated the UBDRS in subjects with JNCL since 2002; during that time, the scale has been refined to improve reliability and validity. Now that therapies are being proposed to prevent, slow, or reverse the course of JNCL, the UBDRS will play an important role in quantitatively assessing clinical outcomes in research trials. METHODS: We administered the UBDRS to 82 subjects with JNCL genetically confirmed by CLN3 mutational analysis. Forty-four subjects were seen for more than one annual visit. From these data, the rate of physical impairment over time was quantified using multivariate linear regression and repeated-measures analysis. RESULTS: The UBDRS Physical Impairment subscale shows worsening over time that proceeds at a quantifiable linear rate in the years following initial onset of clinical symptoms. This deterioration correlates with functional capability and is not influenced by CLN3 genotype. CONCLUSION: The UBDRS is a reliable and valid instrument that measures clinical progression in JNCL. Our data support the use of the UBDRS to quantify the rate of progression of physical impairment in subjects with JNCL in clinical trials.